Foreign direct investment, domestic investment, and growth of manufacturing sector in Pakistan: Aggregate and disaggregate analysis - Rahman, Saif Ur (2022)
This study aims to examine the effects of foreign direct investment (FDI) and domestic private investment (DPI) on growth of manufacturing sector in Pakistan in aggregate and disaggregate settings. The overall manufacturing sector, large-scale and small-scale manufacturing industries are analyzed in aggregate setting. However, in disaggregate setting, four industries from each large-scale and small-scale manufacturing sector are selected. The textile, sugar, cement and chemical industries are selected as large-scale industries while furniture and sports, rubber, tobacco and leather industries are selected as small-scale industries. The study also investigates the interaction effect of institutional quality on the relationship between FDI, DPI and growth of manufacturing sector. By applying the Auto Regressive Distributed Lag (ARDL) approach on the time series data from 1980-2017, the positive and significant effect of FDI and DPI on growth of manufacturing sector is found. Moreover, in disaggregate analysis of large-scale and small-scale manufacturing industries, both FDI and DPI positively and significantly influence the manufacturing growth except sugar and leather industry where the effect of FDI is found to be negative. The results of the interaction effect of institutional quality show that performance of FDI increases with interaction effect of institutional quality. The institutional indicators show positive interaction effect with FDI and DPI on growth of manufacturing sector. The government should develop such economic policies that attract FDI and DPI to facilitate new national and foreign investments through the provision of the necessary infrastructure and appropriate energy supply in Pakistan. Institutional quality should be among the main indicators for devising and executing macroeconomic policies to enhance FDI, DPI and manufacturing growth. Policymakers should pay more attention to maintain government stability and socioeconomic conditions, government effectiveness, control of corruption in order to build a united, peaceful, and harmonious society.